Status Pekerjaan Ibu dan Status Gizi Balita di Posyandu Karya Budi Asih 2B - Fatonah HS, Sofa; Susilawati, Sinta; Faizah, Siti (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2023)
The nutritional status of children under five has a very big influence in creating quality human resources in the future. The nutritional status of children under five is closely related to economic factors. The economic condition of the family depends on the work of both parents. The purpose of this study was to determine the relationship between the mother's employment status and the nutritional status of toddlers at Posyandu Karya Budi Asih 2B, RW 02, Cibeber Village. The research design used was cross-sectional. Data were collected through interviews, then the collected data were analyzed using Fisher's exact test. The results of hypothesis testing show a value of p = 0.00. Furthermore, it was concluded that there was a relationship between employment status and the nutritional status of toddlers.Keywords: toddler; nutritional status; mother's job ABSTRAK Status gizi balita memiliki pengaruh yang sangat besar dalam mewujudkan sumber daya manusia yang berkualitas di masa yang akan datang. Status gizi balita sangat berhubungan dengan faktor ekonomi. Kondisi ekonomi keluarga tergantung dari pekerjaan kedua orang tua. Tujuan penelitian ini adalah untuk mengetahui hubungan antara status pekerjaan ibu dengan status gizi balita di posyandu Karya Budi Asih 2B, RW 02, Kelurahan Cibeber. Rancangan penelitian yang digunakan adalah cross-sectional. Data dikumpulkan melalui wawancara, lalu data yang telah terkumpul dianalisis menggunakan Fisher’s exact test. Hasil pengujian hipotesis menunjukkan nilai p = 0,00. Selanjutnya disimpulkan bahwa ada hubungan antara status pekerjaan dengan status gizi balita.Kata kunci: balita; status gizi; pekerjaan ibu